Towards an Analysis of Who Creates Clone and Who Reuses it - Moriwaki, Takuya; Igaki, Hiroshi; Yamanaka, Yuki; Yoshida, Norihiro; Kusumoto, Shinji; Inoue, Katsuro (Electronic Communications of the EASST, 2014)
Code clone analysis is valuable because it can reveal reuse behaviours efficientlyfrom software repositories. Recently, some code reuse analyses using clonegenealogies and code clones over multiple projects were conducted. However, mostof the conventional analyses do not consider the developers’ individual difference toreuse behaviors. In this paper, we propose a method for code reuse analysis whichtakes particular note of the differences among individuals. Our analysis methodclarifies who reused whose source code across multiple repositories. We believethe result might provide us with constructive perceptions such as characteristics ofreused code itself by multiple developers, and developers who implement reusablecode.